Developing Technical Expertise to Support Synchronous Online Classes: The Columbia University School of Social Work Institute on Technical Skills for Online Event Production - Folk, Krystal; Marquart, Matthea; Backus Florio, Megan; Garay, Kristin (International Journal of Advanced Corporate Learning (iJAC), 2021)
Skilled technical support is essential to enable webinars, synchronous online classes, and other live online events to run smoothly. Having a tech support professional dedicated to preventing and troubleshooting technology issues allows presenters to focus on the substance of online events. This article shares an example of an interactive online training program that develops the technical skills and expertise needed to support live online events hosted on web conferencing platforms. The program, called the Institute on Technical Skills for Online Event Production, blends asynchronous homework and synchronous classes in an intensive, hands-on format. Run by Columbia University School of Social Work’s Online Campus, this Institute trains social workers to become technical support specialists for online courses and events, and the approach is replicable across academic disciplines and for workplaces.